The Use of TiO2-SiO2 in Photocatalytic Process to Degrade Toxic and Dangerous Waste - Destiarti, Lia; Tjokronegoro, Roekmiati; Rakhmawaty, Diana; Rudiyansyah, (Makara Journal of Science, 2015)
This study was conducted to investigate the use of TiO2 immobilized on SiO2 (TiO2-SiO2) in a photocatalytic process to degrade toxic industrial waste, phenol, linear alkylbenzene sulfonate (LAS), and Cr(VI), which is dangerous for humans and the environment. Titanium dioxide (TiO2), as a photocatalyst, can make the solution become turbid. Thus, TiO2-SiO2 was used to increase the possibility of ultraviolet (UV) transmission. The phenol and LAS levels were measured with the Indonesian National Standard (INS) while the Cr(VI) level was determined with the colorimetric method. The activity test for the catalyst in suspension and immobilization against phenol showed that TiO2-SiO2 was more active than TiO2. By using the photocatalytic process with the TiO2-SiO2 photocatalyst for 8 h, degradation of phenol and LAS reached 50% as a single compound and 12% as a mixture. However, TiO2-SiO2 did not decrease Cr(VI)